Sistem Penilaian dalam Pembelajaran - Sovia Mas Ayu (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
All professional teachers should conduct a certain assessment in the end of every learning process. Assessing students’ learning process is an integral part of whole learning process. The kinds of test may take in various forms: oral test, written test, performance, product or portfolio. The test instruments can be in the forms of multiple choice, objective and non-objective essays, short answers or matching the choices.